A carbohydrate approach for the formal total synthesis of (−)-aspergillide C - Srihari, Pabbaraja; Hari Krishna, Namballa; Sridhar, Ydhyam; Kamal, Ahmed (Beilstein Journal of Organic Chemistry, 2014)
An enantioselective formal total synthesis of aspergillide C is accomplished using commercially available tri-O-acetyl-D-galactal employing a Ferrier-type C-glycosylation, utilizing a Trost hydrosilylation and protodesilylation as key reactions.
Keywords: alkynylation; chiron approach; Ferrier-type C-glycosylation; macrolide